The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2022
DOI: 10.1016/j.jmir.2021.12.007
|View full text |Cite
|
Sign up to set email alerts
|

A review of the effectiveness of fever tent setup in COVID-19 pandemic from a radiology perspective

Abstract: Introduction: This paper describes our experience in setting up a dedicated imaging facility within a temporary fever tentage in an acute tertiary hospital in Singapore during the coronavirus disease 2019 (COVID-19) pandemic. We review in detail the effectiveness of the setup and its role from the radiological perspective. Methods: The dedicated imaging facility within the temporary fever tentage was equipped with a computer-on-wheels (COWs) to access patients’ medical records and a portable x-ray m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 15 publications
1
0
0
Order By: Relevance
“…Lastly, we have shown that care is delivered faster in the Covid tent compared to "tent appropriate" patients seen in the main ED, likely due to a streamlined workflow. These results are in line with a recent study which found chest radiographs are obtained more expeditiously in a dedicated 'fever tent' compared to the usual radiography facilities in the setting of the Covid-19 pandemic [10]. An ED with a shorter length of stay and a decreased rate of patients leaving without being seen could impact patient satisfaction.…”
Section: Discussionsupporting
confidence: 88%
“…Lastly, we have shown that care is delivered faster in the Covid tent compared to "tent appropriate" patients seen in the main ED, likely due to a streamlined workflow. These results are in line with a recent study which found chest radiographs are obtained more expeditiously in a dedicated 'fever tent' compared to the usual radiography facilities in the setting of the Covid-19 pandemic [10]. An ED with a shorter length of stay and a decreased rate of patients leaving without being seen could impact patient satisfaction.…”
Section: Discussionsupporting
confidence: 88%